2009
DOI: 10.1007/s00114-009-0545-6
|View full text |Cite
|
Sign up to set email alerts
|

Irresistible bouquet of death—how are burying beetles (Coleoptera: Silphidae: Nicrophorus) attracted by carcasses

Abstract: Chemical composition of volatiles emitted from fresh mouse carcasses (laboratory mice, Mus musculus) was studied using solid sample injection technique (solid-phase micro-extraction), two-dimensional gas chromatography with time of flight mass spectrometric detection and gas chromatography with electroantennographic detection. Electroantennography (EAG) and laboratory olfactometric behavioural observations were used to study the antennal sensitivity to identified infochemicals and their attractiveness for bury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(123 citation statements)
references
References 51 publications
1
120
0
2
Order By: Relevance
“…Carrion beetles have been reported to respond positively to a group of common volatile compounds emitted by different types of fresh carcasses, i.e. sulphur-containing gases, such as methanethiol, dimethyl sulphide, dimethyl disulphide and dimethyl trisulphide (Kalinova et al, 2009). It would be interesting to know whether necrophagous beetles, like coprophagous beetles, orientate towards carcasses through innate olfactory preferences or if larval diet may influence the choices made by adults.…”
Section: Discussionmentioning
confidence: 99%
“…Carrion beetles have been reported to respond positively to a group of common volatile compounds emitted by different types of fresh carcasses, i.e. sulphur-containing gases, such as methanethiol, dimethyl sulphide, dimethyl disulphide and dimethyl trisulphide (Kalinova et al, 2009). It would be interesting to know whether necrophagous beetles, like coprophagous beetles, orientate towards carcasses through innate olfactory preferences or if larval diet may influence the choices made by adults.…”
Section: Discussionmentioning
confidence: 99%
“…The former type is large, round, pit-like, and located on one side of the apical antennomere along its axis; the latter is smaller, hair-like, and distributed on the other side. The identical olfactory structures indicate that silphids in the Jurassic were already adapted to detecting sulfur-containing volatile organic compounds over long ranges, just as in extant nicrophorines and most silphines (15). Mesozoic silphids thus may have been significant scavengers and important to the breakdown and recycling of carcasses in such ancient ecosystems.…”
Section: Significancementioning
confidence: 95%
“…A variety of collection methods are available including solid-phase microextraction (SPME) (Hoffman et al 2009 ;Kalinova et al 2009 ;DeGreeff and Furton 2011 ;Cablk et al 2012 ), thermal desorption (TD) (Vass et al 2004 ;Statheropoulos et al 2005Statheropoulos et al , 2007Vass et al 2008 ;Stadler et al 2013 ) and solvent desorption Dekeirsschieter et al 2009Dekeirsschieter et al , 2012. Although all of these sampling methods utilize a solid sorbent to trap the VOCs they each have particular advantages and disadvantages.…”
Section: Analysis Of Decomposition Vocsmentioning
confidence: 99%
“…Comprehensive two dimensional gas chromatography (GC × GC) is an emerging technique that provides the additional peak capacity required for the analysis of complex samples, however its wide range of potential applications are not well represented in the literature (Dalluge et al 2003 ). Recent studies into decomposition odour have shown the applicability of this analytical technique to this complex sample type (Kalinova et al 2009 ;Brasseur et al 2012 ;Dekeirsschieter et al 2012 ;Stadler et al 2013 ).…”
Section: Analysis Of Decomposition Vocsmentioning
confidence: 99%
See 1 more Smart Citation